Platforms of climate change: an evolutionary perspective and lessons for Malaysia - Koh, Fui Pin; Joy, Jacqueline Pereira; Sarah Aziz, (Universiti Kebangsaan Malaysia, 2013)
The discourse on climate change of both natural and anthropogenic origins has a long history and the subject has been discussed from both scientific and social perspectives. This paper reports on a study that begins with a review of the historical perspective of the subject with a focus on the enhanced greenhouse effect from the 15th to 19th centuries by identifying the main discussion platforms and delineating their temporal and substantial interactions. The three main climate change platforms are the science platform, the media platform and the policy platform. The science platform is where theories related to the greenhouse effects and their enhancements are developed. The media platform comprises newspaper coverage on climate change themes, while the policy platform is mainly the UN and its decisions relating to climate change. The authors assert that if not for the discussion, attention and actions within each, the climate change discussion would not have become so intense and the climate change agenda would not have been furthered. It is observed that less attention is given to science-media interaction compared to science-policy interaction. Similarly, NGOs have received little attention in these platforms and their interactions. The second part of the paper presents a descriptive case study that was undertaken to discuss the climate change agenda at a national level to determine whether the national scenario will have a pathway similar to that of the global one. It is suggested that in Malaysia this agenda is more likely to be driven by policy. The country’s climate change policy is expected to address the needs and gaps identified in this study.